THE MEDIATING IMPACT OF ORGANIZATIONAL COMMITMENT ON THE INFLUENCE OF LEADERSHIP BEHAVIOR AND WORK ENVIRONMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT AJB BUMIPUTERA 1912 HEADQUARTER - Arviyah, Sova; Johanes Lo, Singmin (Dinasti International Journal of Management Science, 2020)
This research aimed to analyze the mediating role of organizational commitment on the influence of leadership behavior and work environment towards organizational citizenship behavior. The research was conducted from October 2019 to April 2020 at AJB Bumiputera 1912 Headquarter. The populations in this research were 317 employees. There were 177 employees were taken as sample using Slovin’s formula with 5% error tolerance. Then, a quota sampling method was used in administering questionnaires to respondents. Data collected were analyzed using Structural Equation Modeling with the help of SmartPLS software version 3.2.8 for Windows. The results showed that leadership behavior had a slight positive, but not significant influence on organizational citizenship behavior. However, work environment had a positive and significant influence on organizational citizenship behavior. Meanwhile, the organizational commitment had positively and significantly mediated the influences of both leadership behavior and work environment on organizational citizenship behavior.